Harmonization potential of the fragmented farmlands in Finland: The pros and cons for critical parcel characteristics - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri; Näsi, Roope; Puttonen, Eetu; Honkavaara, Eija (Elsevier, 2024)
Agricultural landscapes have been shaped by gradual, partially optimized changes in farms and surrounding areas which have resulted in fragmented agricultural landownership and increased distances on farms. Since Finland joined the EU in 1995, the average farm size has more than doubled which has increased the distances on farms. This may have caused trade-offs with resource use efficiency, productivity, and sustainability. The aim of this study was to evaluate the potential and impacts of land reallocation by integrating regional variability, logistical factors, and emerging satellite imagery, with an emphasis on enhancing resilience in future climates. This study estimated the theoretical potential for land reallocation between farms to reduce farmland fragmentation but also applied fixed land exchange rates (5 % to 40 %) with the primary aim to reduce distances within each farm depending on the farm size and region. The aim was also to identify co-benefits and trade-offs on the number of parcels in a farm, the production capacity of exchanged parcels, diversification potential, and the proximity of parcels to waterways. While keeping the farm size constant, large potential was found to optimize fragmented landscapes and reduce distances within farms especially on large farms. However, only a moderate exchange rate of 5 % almost halved the distances in the best cases of the farms, while exchange rates >20 % provided less additional logistic benefits. Thereby, modest, well targeted measures are not only more acceptable to landowners but may provide the most benefits with fewer trade-offs. In unsatisfactory cases, large parcels were replaced by higher numbers of smaller ones, productivity differences occurred, and closer parcels became more uniform, which may reduce diversification options, which are important for resilience and sustainability. Hence, merging and reshaping nearby parcels after reallocation might be needed to complete rationalization. Estimated changes in the proximity of the parcels to waterways tended to improve the farmers’ readiness to implement irrigation as an adaptation measure to climate change. The variable outcome of parcel reallocation emphasizes the central role of the current customer-driven consolidation system chaired by independent land surveyors to boost the land reallocation also in the future to improve logistics, resource efficiency, and sustainability on farms that today struggle with cost-crises.
Keywords: diversification; land exchange; productivity; distance to farm center; field size; irrigation